Peran Zenius sebagai Aplikasi Berbasis Mobile dalam Perkembangan Bahasa Indonesia pada Siswa SMA - Syifa Fauziah Rahmah; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2024)
Zenius is a mobile-based application that provides many conveniences for its users in learning. Zenius is present as a new technology, namely a popular learning application that helps and supports students in the learning process. Today's high school students definitely have devices with adequate specs to access many applications. One of the correct uses of technology is that students know what applications are able to support their development in learning. The aim of this research is to explain the role of the features presented by Zenius in Indonesian language learning, especially in developing high school students' language skills. The method used is a descriptive-analytical literature method and also interviews with high school students. In this research, it was found that the usefulness of the features in the Zenius application plays a very important role in the development of students' language skills.